Domain Wall Magnetoresistance in Nanowires: Dependence on Geometrical Factors and Material Parameters - Altbir-Drullinsky, D; Retamal-Abarzua, J; Allende-Prieto, S (2014)
The magnetoresistance associated with the presence of domain walls in metallic nanowires is investigated as a function of geometrical parameters, corresponding to the wall thickness and the nanowire width, as well as of material parameters, such as the band filling and the exchange interaction. Transport across the structure is described within Landauer formalism. Both cases of saturated and non-saturated ferromagnets are considered, and in all of them the contributions from spin-flip and non-spin-flip are separately analyzed. It has been found that for certain range of parameters deviations in the normalized magnetoresistance as high as 20% may be achieved. In addition, it has been shown that the spin-flip process is dependent on the wall thickness. © 2013 Elsevier B.V.
Keywords: Magnetoresistance; Nanowires; Domain walls